Pengambilan Keputusan pada Saat Krisis dan Perilaku dalam Organisasi - Fitri Handayani Sitorus Pane; Sylviana Siregar (Universitas Muhammadiyah Enrekang, 2022)
Research in this journal aims to find out how to make good decisions during a crisis, as well as how to behave in an organization. As for this study using qualitative methods with the type of study document/text research. The results described in the discussion are that what leaders need when a crisis occurs is not pre-planned handling, but behavior and mindset that can prevent overreaction to crises and how to deal with future challenges.